(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
In the context of India, this article looks at the education of children from marginalized communities, with a focus on children with incapacities. Various educational arrangements for the children with incapacities are addressed based on an examination of post independences government papers. It delves into the Indian government’s attempts to establish special schools, as well as its integration initiatives and more current prominence on comprehensive education. It also tries to define "inclusive education" as it is defined in different government publications. The essay ends by stating that a contextual knowledge of inclusive education is required in order to address India’s present educational problems. In 1947, the year India gained independence, the Indian Constitution included education as a guiding idea rather than a basic right. While everyone has basic human rights and freedoms, which take precedence above any other legislation of the place, directive concepts are said to be important in the workings of government but are not legally valid.